KNOWLEDGE, ATTITUDE AND PRACTICE OF NURSES REGARDING POST-OPERATIVE PAIN MANAGEMENT AT THE HOSPITAL - DIN , SU; SADDIQUE , H; TASNEEM , SS (Biological and Clinical Sciences Research Journal, 2024)
Post-operative pain management is a critical aspect of nursing care that significantly impacts patient recovery and satisfaction. In resource-limited settings like Pakistan, nurses often face challenges due to inadequate training, limited resources, and cultural misconceptions, leading to gaps in effective pain management practices. Objective: This study aimed to assess the knowledge, attitudes, and practices of nurses regarding post-operative pain management in a tertiary care hospital in Pakistan. Methods: A descriptive cross-sectional study was conducted among 140 nurses working in surgical wards, ICUs, and postoperative units. Participants were selected through convenience sampling, and data were collected using a structured, prevalidated questionnaire. The questionnaire included sections on demographic information, knowledge, attitudes, and practices related to post-operative pain management. Data were analyzed using SPSS version 26, with descriptive and inferential statistics employed to summarize findings and identify associations. Results: The study revealed moderate knowledge levels among participants, with 56.4% recognizing the appropriate use of opioids for pain relief and 50% agreeing that increasing analgesic doses may indicate psychological dependency. Positive attitudes toward pain management were noted, with 37% acknowledging the effectiveness of non-pharmacological interventions. However, gaps in practices were evident, with only 42.9% consistently using pain assessment tools. Education and experience significantly influenced knowledge and practices (p < 0.05).Conclusion: While nurses demonstrated adequate knowledge and positive attitudes, significant gaps in practices and specific knowledge areas were identified. Targeted training programs, policy reforms, and culturally sensitive educational interventions are essential to enhance pain management competencies among nurses and improve patient outcomes in surgical settings.